Magnetic resonance imaging of human knee joint functionality under variable compressive in-situ loading and axis alignment. (October 2020) - Schad, Philipp; Wollenweber, Maximilian; Thüring, Johannes; Schock, Justus; Eschweiler, Jörg; Palm, Giulia; Radermacher, Klaus; Eckstein, Felix; Prescher, Andreas; Kuhl, Christiane; Truhn, Daniel; Nebelung, Sven
Abstract: Magnetic resonance imaging (MRI) under mechanical loading, commonly referred to as stress MRI, allows the evaluation of functional properties of intra- and periarticular tissues non-invasively beyond static assessment. Quantitative MRI can identify physiological and pathological responses to loading as indication of, potentially treatable, early degeneration and load transmission failure. Therefore, we have developed and validated an MRI-compatible pressure-controlled axial loading device to compress human knee specimens under variable loading intensity and axis deviation. Ten structurally intact human knee specimens (mean age 83.2 years) were studied on a 3.0T scanner (Achieva, Philips). Proton density-weighted fat-saturated turbo spin-echo and high-resolution 3D water selective 3D gradient-echo MRI scans were acquired sequentially at 10° joint flexion in seven configurations: unloaded and then at approximately half and full body weight loading in neutral, 10° varus and 10° valgus alignment, respectively. Following manual segmentation in both femorotibial compartments, cartilage thickness (ThC) was determined as well as meniscus extrusion (ExM). These measures were compared to computed tomography scans, histological grading (Mankin and Pauli scores), and biomechanical properties (Instantaneous Young's Modulus). Compartmental, regional and subregional changes in ThC and ExM were reflective of loading intensity and joint alignment, with the greatest changes observed in the medial compartment during varus and in the lateral compartment during valgus loading. These were not significantly associated with the histological tissue status or biomechanical properties. In conclusion, this study explores the physiological in-situ response of knee cartilage and meniscus, based on stress MRI, and as a function of loading intensity, joint alignment, histological tissue status, and biomechanical properties, as another step towards clinical implementation. Graphical abstract: Image 1 Highlights: Stress MRI techniques allow functional assessment of knee joint structures. A dedicated device for in-situ loading of human cadaveric knee joints was developed. Imaging biomarkers, e.g. cartilage thickness, are related to loading parameters. Loading intensity and alignment affect cartilage and meniscus responses to loading. Histological and biomechanical measures are unrelated to responses to loading.